PENGARUH KEPERCAYAAN DAN TEKNOLOGI TERHADAP KINERJA OPERASIONAL YANG DIMEDIASI OLEH KOLABORASI RANTAI PASOKAN PADA USAHA KECIL DAN MENENGAH DI KOTA BANDA ACEH - Mustika Apryani; Sofyan Idris (Departemen Manajemen, 2021)
The purpose of this study is to discover the effect of Trust and Technology towards Operational Performance mediated by Supply Chain Collaboration. The population used in this study were Small and Medium manufacturing Enterprises within Banda Aceh city it consists approximately 910 businesses, but only 278 are taken as samples. The sampling technique being used on data gathering is proportional stratified random sampling. The tool being used on data gathering is questionnaire. The Structural Equation Modeling is used on analytical method to determine the effect of variables involved. The result shows that Trust is not impacted significantly to the Operational Performance, but it has a significant effect on Supply Chain Collaboration. Technology has a significant effect on the Operational Performance and technology has a significant effect on Supply Chain Collaboration. This study also find that Supply Chain Collaboration is not impacted significantly to the Operational Performance. Trust mediated by Supply Chain Collaboration is not affected to Operational Performance. And, Technology Mediated by Supply Chain Collaboration is not affected significantly to Operational Performance.